PUPPET THEATRE FOR MIDDLE SCHOOL: HISTORY, MAIN TECHNIQUES, AND PROPOSALS FOR THE 6TH GRADE - Neris, Kleriston Luis Rocha (Seven Editora, 2026)
This article briefly addresses the history and main types of Puppet Theatre, as well as its potential for pedagogical use in Art classes with 6th-grade students in Elementary School II. The research is justified by the scarcity of references on the subject in Maranhão, especially in São Luís, regarding the history and techniques of puppet making, a gap that has been partially filled by initiatives of the Casemiro Coco Group. In the educational field, puppet theatre is presented as a powerful methodology for teaching Art, as it integrates sensitivity, corporeality, and critical thinking, in accordance with the National Common Curricular Base. The overall objective of this research is to analyze Puppet Theatre in its main forms, techniques, and pedagogical possibilities, understanding its potential as an artistic language in the teaching of Art in Basic Education. Methodologically, this is a qualitative, exploratory, and descriptive-interpretative research, aimed at understanding Puppet Theatre and its pedagogical contributions. It was concluded that Puppet Theatre, as a plural and historically relevant artistic language, possesses significant pedagogical potential because, by integrating body, object, and imagination, it expands the expressive possibilities of students and fosters meaningful aesthetic experiences.